HSF1 is involved in immunotherapeutic response through regulating APOJ/STAT3-mediated PD-L1 expression in hepatocellular carcinoma. Issue 1 (31st December 2023) - Cheng, Hongxia; Wang, Sikai; Huang, Aidan; Ma, Jing; Gao, Dongmei; Li, Miaomiao; Chen, Huaping; Guo, Kun
ABSTRACT: Hepatocellular cancer (HCC) is a serious illness with high prevalence and mortality throughout the whole world. For advanced HCC, immunotherapy is somewhat impactful and encouraging. Nevertheless, a substantial proportion of patients with advanced HCC are still unable to achieve a durable response, owing to heterogeneity from clonal variability and differential expression of the PD-1/PD-L1 axis. Recently, heat shock factor 1 (HSF1) is recognized as an important component of tumor immunotherapeutic response as well as related to PD-L1 expression in cancer. However, the mechanism of HSF1 regulating PD-L1 in cancer, especially in HCC, is still not fully clear. In this study, we observed the significantly positive correlation between HSF1 expression and PD-L1 expression in HCC samples; meanwhile combination expressions of HSF1 and PD-L1 served as the signature for predicting prognosis of patients with HCC. Mechanistically, HSF1 upregulated PD-L1 expression by inducing APOJ expression and activating STAT3 signaling pathway in HCC. In addition, we explored further the potential values of targeting the HSF1-APOJ-STAT3 axis against CD8 + T cells-mediated cancer cells cytotoxicity. These findings unveiled the important involvement of HSF1 in regulating PD-L1 expression in HCC as well as provided a novel invention component for improving the clinical response rate and efficacy of PD-1/PD-L1 blockade.